Propofol effects on the morphology of rat testes subjected to testicular ischemiareperfusion - Urt Filho,Antônio (2012)
PURPOSE: To evaluate the effects of propofol as an inhibitor of tissue injury in testicular ischemia-reperfusion in rats. METHODS: 30 Wistar rats were assigned to one of three groups of 10 animals: G1, testicular exposure alone; G2 and G3: testicular ischemia caused by left spermatic cord torsion of 720º. In G3, propofol was administered intraperitoneally at 20 mg/kg/h 45 minutes after spermatic cord torsion. In G2 and G3, spermatic cords were detorsioned after 60 min. In all three groups, testes were subsequently repositioned in the scrotum. After 90 days, bilateral orchiectomy was performed for histological examination. RESULTS: No abnormalities in seminiferous tubules were found in G1. In G2, 86.6% of left testes exhibited abnormalities, in contrast with 67.8% for right testes. In G3, these proportions were 57.3% and 45.6%, respectively. A statistically significant difference was found between G2 and G3. CONCLUSION: Propofol reduced the tissue damage in rat testes subjected to ischemia-reperfusion caused by spermatic cord torsion.